A construção do imaginário anticomunista em Passo Fundo : o olhar da imprensa sobre o final da segunda guerra mundial e o início da guerra fria - Ferron, José Altemir da Luz (2008)
The objective of this Word is to observe the apprehension of the in relation to the end of the Word War II and the beginning of the Cold war considering the international, national and regional moment in the forties, using the written press ay mediator. The pieces of information that came to Passo Fundo city society had as basis notes, reportages, articles and opinions which were published by O Nacional and Diário da Manhã news papers. The time cutting of this word covers the period between 1945 and 1949 and aims to observe how the themes related to the international situation had influence in the regional environment. This research has as objective to show how Passo Fundo city press, represented by these news papers is going to talk about the chief events related to the end of the Word War II and the beginning of the Cold War and how this is going to result in a campaign whose principal objective was the formation of the political and ideological regional conception which had anti-communism as main objective